Effects of combinations of curcumin, linalool, rutin, safranal, and thymoquinone on glucose/serum deprivation-induced cell death - Alinejad, Bagher (Mashhad University of Medical Sciences, 2013)
Objective: Several phytochemical agents have been known to exhibit a neuroprotective effect. Among them, curcumin, linalool, rutin, safranal, and thymoquinone were widely investigated and neuroprotective activity of each of them was shown by several studies. This work was planned to investigate whether different combinations of them could induce better neuroprotective effect against glucose/serum deprivation (GSD)-induced cytotoxicity. Materials and Methods: PC12 cells were cultivated for 8 h in GSD condition in both the absence and presence of curcumin, linalool, rutin, safranal, thymoquinone, or combinations of them. At the end of the experiment, the cell viability was determined using MTT assay. Results: The cells cultured in GSD condition showed a significant decrease in viability (28±1%) as compared with those cultured in standard condition (100±2%). In the presence of curcumin (10 µg/ml), linalool (16 µg/ml), rutin (200 µg/ml), safranal (50 µg/ml), and thymoquinone (1 µg/ml), the cell viability increased to 69±3.4% (p<0.001), 44±1.4% (p<0.01), 64±0.5% (p<0.001), 49±2% (p<0.001), and 70±3.2% (p<0.001), respectively. When different combinations of the agents were tested, the best cytoprotective activity was obtained from safranal + curcumin + thymoquinone (97±5%, p<0.01 vs. untreated cells). Conclusions: The present study demonstrated that a combination of safranal + curcumin + thymoquinone can block GSD-induced cell death and has the potential to be considered for management of cerebral ischemia and neurodegenerative diseases.